2020
DOI: 10.1007/s10526-020-10015-0
|View full text |Cite
|
Sign up to set email alerts
|

Field performance of the parasitoid wasp, Trichogrammatoidea armigera (Hymenoptera: Trichogrammatidae) following releases against the millet head miner, Heliocheilus albipunctella (Lepidoptera: Noctuidae) in the Sahel

Abstract: The effectiveness of the egg parasitoid Trichogrammatoidea armigera Nagaraja (Hymenoptera: Trichogrammatidae) in controlling Heliocheilus albipunctella de Joannis (Lepidoptera: Noctuidae), a major insect pest of pearl millet in the Sahel was assessed during two consecutive years in Niger on-station and on-farm conditions. We found that released T. armigera were able to find and parasitize host eggs within pearl millet fields both onstation and in farmers' fields. On-station releases of T. armigera led to an av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…This corresponds to 100 sorghum plants infested in each plot (25%). The plants were infested 2 weeks after planting using the sentinel egg technique [20,33,34]. Freshly laid egg masses of FAW were removed from sorghum leaves in the laboratory culture, taken to the field, and pasted to the upper face of sorghum leaves with nontoxic glue to mimic naturally laid eggs.…”
Section: On-station Releasesmentioning
confidence: 99%
“…This corresponds to 100 sorghum plants infested in each plot (25%). The plants were infested 2 weeks after planting using the sentinel egg technique [20,33,34]. Freshly laid egg masses of FAW were removed from sorghum leaves in the laboratory culture, taken to the field, and pasted to the upper face of sorghum leaves with nontoxic glue to mimic naturally laid eggs.…”
Section: On-station Releasesmentioning
confidence: 99%
“…Functional response studies are essential to determine the searching efficiency of a given natural enemy, however, they need to be corroborated through field studies. Other characteristics like spatial complexity in nature, host traits, biotic and abiotic factors and plant varieties can also influence the behaviour and efficiency of natural enemies (Karimoune et al, 2020; Manohar et al, 2020; Silva et al, 2022). It is reported that the maximum parasitism of a high‐temperature tolerant strain and local Ludhiana strain of T. chilonis showed a negative and positive correlation with temperature and relative humidity, respectively (Singh & Shenhmar, 2008).…”
Section: Discussionmentioning
confidence: 99%